Contribuições da educação alimentar e nutricional junto a um grupo de idosos - Criscuolo, Carolina [UNESP]; Monteiro, Maria Iolanda; Telarolli Júnior, Rodolpho [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The aim of this study was to evidence the main contributions of the Food and Nutrition Education related to the problematical education by Paulo Freire among an elderly group. The work was based on the Case Study methodology, of qualitative research, with its main instruments: interviews and group meetings. Nine meetings were held to discuss about food and nutrition with a group of nine elderly, in the Open University for the Third Age, in Araraquara / SP, during three months, from August to October 2007. The results were analyzed by the content analysis method. The research identifi ed that all participants sought relevant information to their current life phase and these expressed intentions to share them. As for themes discussed, the most important and interesting considered for the group was about healthy eating. In this aspect, just two individuals reported that hadn’t socioeconomic conditions to have an adequate food. In the sensitization process was possible to promote the appropriation of thematic contents by the group and, by the refl ection, previous knowledge could be consolidated and expanded. The results evidence that the Food and Nutrition Education, based in problematization, can be pointed as one of possible alternatives for the knowledge construction more effectively, facilitating the social interaction and the better control of chronic diseases. The conclusion is that educational proposals like this can contribute to the arguments and development public policies or actions plans for the elderly health.

O objetivo deste estudo foi evidenciar as principais contribuições da Educação Alimentar e Nutricional (EAN) associada à educação problematizadora de Paulo Freire junto a um grupo de idosos. O trabalho foi pautado na metodologia do Estudo de Caso, da pesquisa qualitativa, com os seus principais instrumentos: entrevistas e encontros em grupo. Foram realizados nove encontros para discussão sobre alimentação e nutrição com um grupo de nove idosos, na Universidade Aberta à Terceira Idade, do Município de Araraquara/SP, no período de três meses, de agosto a outubro de 2007. Os resultados foram analisados através do mé- todo de análise de conteúdo. A investigação identifi cou que todos os participantes buscavam informações relevantes para a fase atual da vida e esses expressaram intenções de partilhá-las. Quanto às temáticas abordadas, a considerada mais importante e de maior interesse pelo grupo foi sobre a alimentação saudável. Nesse aspecto, apenas dois idosos afi rmaram não ter condições socioeconômicas para realizar uma alimentação adequada. No processo de sensibilização foi possível promover a apropriação dos conteúdos temá- ticos pelo grupo e, por meio da refl exão, conhecimentos anteriores puderam ser consolidados e ampliados. Os resultados evidenciam que a EAN, pautada na problematização, pode ser apontada como uma das alternativas possíveis para a construção do conhecimento de forma mais efetiva, com vistas ao favorecimento do convívio social e de um melhor controle das doenças crônicas não-transmissíveis. Concluise que propostas educativas como esta podem contribuir para a fundamentação e elaboração de políticas públicas ou planos de ações voltadas para a saúde do idoso.
Food and nutrition education contributions among an elderly group
Keywords: Food and nutrition education; Aged; Health education; Health of the elderly; Qualitative research; Educação alimentar e nutricional; Idoso; Educação em saúde; Saúde do idoso; Pesquisa qualitativa